State Systems for Skill Development in India : A Study of Bihar, Gujarat, Rajastha, and Maharashtra - World Bank (Washington, DC, 2016)
At a time when the World’s leading economies are rapidly greying, India is set to have the largestand youngest workforce the world has ever seen. Indeed, by 2020, when the global shortage ofmanpower soars to 57 million, India is expected to be the world’s leading provider of human resources, with a surplus of 46 million working-age people. However, this window of opportunity will not just be rare, it will also be short-lived, since it is predicted to only last until 2040.It is in this context that Prime Minister Modi has made it a national priority to make India the skill capital of the world.The report endeavors to identify the institutional and systemic structures that will be needed to improve the effectiveness of skills training across India’s states. It also seeks to pinpoint innovative best practices and outline ways to scale them up throughout the country.The report covers skill development institutional structures at the state level (in most cases, the State Skill Development Missions), economic zones and future high-growth industries in those zones,corporate engagement in skill development, and finally, innovation in skilling models by states and the corporate sector. In addition, the report also describes some best practices observed globally, especially from Australia, Germany, Japan and South Korea. These models cover three areas of resource optimization pertaining to increasing apprenticeships and industry participation, leveraging technology, and providing training at the grassroots. The key lesson learned is that skilling is a highly localized issue, and models need to be adapted to target groups rather than be force-fitted using a one-size-fits-all kind of approach. Finally, it must be pointed out that high-level recommendations have been provided to enhance the skill development landscape, particularly at the state level, from an institutional and systemic point of view.